Viable Ileosigmoid Knotting, A Very Phenomenon Finding and Rare Cause of Intestinal Obstruction: A Case Report and Literature Review - Beyene SA; Bogale NT; Abdinasir MM; Desalegne AZ; Wossen MA (International Medical Case Reports Journal)
Sintayehu Asrat Beyene,1 Nahom Tadesse Bogale,1 Mahad Mohammed Abdinasir,1 Addisu Zegeye Desalegne,2 Megdelawit Ayalew Wossen3 1General Surgery Unit, Department of Surgery, Jigjiga University Sheik Hassen Yabare Comprehensive Specialized Hospital, Jigjiga, Ethiopia; 2Department of Radiology, Jigjiga University Sheik Hassen Yabare Comprehensive Specialized Hospital, Jigjiga, Ethiopia; 3School of Medicine and Health Sciences, Jigjiga University Sheik Hassen Yabare Comprehensive Specialized Hospital, Jigjiga, EthiopiaCorrespondence: Sintayehu Asrat Beyene; Nahom Tadesse Bogale, Email sintayehubeyene54@gmail.com; Tadnahi2@gmail.comIntroduction: Ileosigmoid knotting is the wrapping of an active component of either the ileum or the sigmoid colon over each other. It is an unusual cause of intestinal obstruction, accounting for 1– 2% of cases of all mechanical obstruction in the majority published literatures. A viable knot is a unique phenomenon of this seldom cause of bowel obstruction.Case Presentation: A sixteen-year-old female patient presents with a complaint of central abdominal distension and obstipation of 12-hour duration. Later, she also developed abdominal cramps and vomiting of ingested matter. Her vital signs were all in the normal range, and the abdominal examination was positive for a grossly distended abdomen with mild upper and central abdominal tenderness. The ileosigmoid knotting was clearly visible on the computed tomography. Emergency exploratory laparotomy was performed, and a viable ileosigmoid knot was identified. Unknotting, derotation, and decompression of the sigmoid colon were performed. The postoperative course was uneventful.Discussion: Ileosigmoid knotting is a rare, life-threatening cause of intestinal obstruction with rapid progression to intestinal vascular compromise and gangrene. It is a hyperactive segment of ileum that winds around the pedicle of the redundant sigmoid colon, resulting in a closed-loop obstruction. There are different classification schemes of ileosigmoid knotting depending on the active component of the knot and based on the viability of the bowel and physiology of the patient. Preoperative diagnosis of this condition is often challenging and usually confirmed intraoperative.Conclusion: A high index of suspicion and prompt surgical exploration are crucial for the best outcome of the patient. Despite being a rare cause of intestinal obstruction, ileosigmoid knotting poses a significant morbidity and mortality to the patient. Management of a patient with viable ileosigmoid knotting is controversial, as some scholars suggest non-resective options and others recommend resective treatment as a recurrence preventive measure.Keywords: ileosigmoid knotting, intestinal obstruction, acute abdomen, volvulus, unknotting, operative decompression, viable